PENGARUH AKUNTABILITAS DAN PENGELOLAAN ALOKASI DANA DESA TERHADAP PENINGKATAN PEMBANGUNAN DESA PADA DESA BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Walmi Sholihat (LPPM Press STIE Indragiri Rengat, 2018)
This research was conducted at Buluh Rampai Village, Seberida District, Indragiri Hulu Regency. The research took place for six months. The purpose of this study was to determine the effect of partial accountability on increasing village development in the Village of Buluh Rampai, Seberida District, Indragiri Hulu District. To find out the effect of partial village fund allocation management on increasing village development in Buluh Rampai Village, Seberida District, Indragiri Hulu Regency. And to find out the influence of accountability and management of the allocation of village funds simultaneously to increase village development in the village of Buluh Rampai, Seberida District, Indrgiri Hulu Regency. In this study, a sample of 95 respondents namely the head of the family of Buluh Rampai Village, Seberida District, Indragiri Hulu Regency. Analysis of the data used in this study is a qualitative analysis using the SPSS Version 24.00 application. The results of multiple linear regression analysis obtained Y = 18.837 + 0.315X1 0.114X2, a = 18.837. Partial test results (T Test) obtained the value of the Accountability variable with tcount> ttable is 2.503> 1.98580 based on the criteria meaning Accountability partially influences the Development of Village Development, and obtained the value of the variable Management of Village Fund Allocation tcount> ttable ie -0.737> -1 98580, based on criteria, means that Village Fund Allocation Management partially has no effect on the Improvement of Village Development. Simultaneous test results (F) obtained value of Fcount> Ftable is 3.209> 3.10 then from the data testing criteria it can be seen that HO is rejected and Ha is accepted, meaning that Accountability and Management of Village Fund Allocation affect the Improvement of Village Development. The results of the calculation of R, obtained value of r or correlation is 0.225 or it has a weak and unidirectional relationship between Accountability and Management of Village Fund Allocation with Increased Village Development, and obtained R square value or coefficient of determination is meaning that the contribution to Village Development Increases is 6.5 % while the remaining 93.5% is explained by other independent variables which are not thorough.